2010
DOI: 10.1016/j.ccr.2010.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ATM/Chk2/p53 Pathway Components Accelerates Tumor Development and Contributes to Radiation Resistance in Gliomas

Abstract: Maintenance of genomic integrity is essential for adult tissue homeostasis and defects in the DNA-damage response (DDR) machinery are linked to numerous pathologies including, cancer. Here we present evidence that the DDR exerts tumor suppressor activity in gliomas. We show that genes encoding components of the DDR pathway are frequently altered in human gliomas and that loss of elements of the ATM/Chk2/p53 cascade accelerates tumor formation in a glioma mouse model. We demonstrate that Chk2 is required for gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
172
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(184 citation statements)
references
References 57 publications
10
172
0
2
Order By: Relevance
“…This limited, delayed apoptosis in response to IR contrasts sharply with the high levels of apoptosis observed in the more radiosensitive medulloblastoma brain tumor (9). Previous experiments demonstrated that this radiation dose confers only a modest survival benefit of ∼15 d in this model, consistent with the radioresistant phenotype of human GBM and the comparatively minimal apoptosis observed in these experiments (21).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…This limited, delayed apoptosis in response to IR contrasts sharply with the high levels of apoptosis observed in the more radiosensitive medulloblastoma brain tumor (9). Previous experiments demonstrated that this radiation dose confers only a modest survival benefit of ∼15 d in this model, consistent with the radioresistant phenotype of human GBM and the comparatively minimal apoptosis observed in these experiments (21).…”
Section: Resultsmentioning
confidence: 53%
“…We chose to use a single dose of radiation to enable time course studies after radiation, and had previously shown that a single dose of 10-Gy radiation induces cell cycle arrest in these tumors (21). Tumor-bearing mice were subjected to a single dose of 10-Gy total body ionizing radiation (IR), and tumor tissue was collected at time points after treatment for immunohistochemical staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of heterozygosity has been found in several chromosomes in patients with glioma using molecular analysis. Many of these chromosomal segments contain known tumor-suppressor genes (17,18), such as p16 on 9p, p53 on 17p and RB on 13q. More recently, SLC22A18 was located within the 11p15.5 cluster, and has been assigned a number of different nomenclatures (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to non stem-like glioma cells, the GSCs have higher activity of cell cycle checkpoints (Bao et al 2006). Therefore, GSCs are more resistant to radiation therapy than differentiated tumor cells (Bao et al 2006;Squatrito et al 2010). GSCs represent a small subpopulation of GBM cells, with the stem-like properties and the capacity of multi-lineage differentiation, self-renewal and exact recapitulation of the original tumor.…”
mentioning
confidence: 99%